Akibat Hukum Bagi Pekerja yang Melanggar Kewajiban Employee Branding Dalam Hubungan Kerja - Suzana, Merillyn Victoria; Ambarwati, Mega Dewi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Employee branding is an important concept in employment relations that aims to strengthen the company's image through employee behavior and attitudes. In the context of employment relations in Indonesia, employees have an obligation to maintain the company's image in accordance with legal provisions and company regulations. This article discusses the legal regulations regarding employee branding obligations in employment relations and the legal consequences for employees who violate these obligations. Based on normative analysis, it was found that violations of employee branding obligations can result in legal sanctions, both internally and externally, including termination of employment (PHK), administrative sanctions, and claims for compensation.